(3SfO GdTjN Ydi Hf CMeO Hf ecQe Gddg GdUYjOi GdYOhi GdeGdci GdCRgQi GdeJhaj SfI (B1189(3g`s - (3Ydj Hf CMeO Hf ecQe GdUYjOj GdYOhj,J (B1189 (3g` s
(3ChdgG (B:s
(3hHYO deG cGf GdSfO ef GdOjf CQOJ Cf CPcQ ai gPG GdKHJ LedI ef CSGfjO eTGjNi s
(3BNQgG (B:s
(3hGdfbJUQ Ydi gPG GdbOQ , hGdMeO ddg QH GdYGdejf , hUdi Gddg Ydi SjOfG eMeO GdfHi GdCei hYdi Bdg hUMHg hSde Bejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B77 - (3U(B97s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B260 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B29s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B234 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(323 (3c(B) s
Keywords: (3GdJGQjNs